2011
DOI: 10.1002/cmdc.201100361
|View full text |Cite
|
Sign up to set email alerts
|

The Tubulin Colchicine Domain: a Molecular Modeling Perspective

Abstract: Computational approaches have been increasingly applied to drug design over the past three decades and have already provided some useful results in the discovery of anticancer drugs. Given the increased availability of crystal structures in recent years, a growing number of molecular modeling studies on tubulin have been reported. Herein we present a brief overview of the role played by computational methods in anti-tubulin research, specifically in the context of colchicine binding agent research. An overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 76 publications
5
131
0
3
Order By: Relevance
“…The residue was purified by means of silica gel column chromatography (hexane/ethyl acetate = 4/1) and PTLC (hexane/ethyl acetate = 4/1) to give 28 (21.8 mg, 30.3%) as a colorless oil. 1 (29) To a mixture of 1-(3-(benzyloxy)-4-methoxyphenyl)-1-(3,4,5-trimethoxyphenyl)siletane (26b) (201.9 mg, 0.45 mmol) and ethyl acetate (5 mL) was added 5% Pd/C (20 mg) at room temperature, and the whole was stirred under an H 2 atmosphere at the same temperature for 13 h. The reaction mixture was filtered through a Celite pad and the solvent was evaporated. The residue was purified by silica gel column chromatography (hexane/ethyl acetate = 9/1 to 4/1) to give 29 (48.5 mg, 30.0%) as a colorless oil.…”
Section: -((34-dimethoxyphenyl)dimethylsilyl)-2-methoxyphenol (22)mentioning
confidence: 97%
“…The residue was purified by means of silica gel column chromatography (hexane/ethyl acetate = 4/1) and PTLC (hexane/ethyl acetate = 4/1) to give 28 (21.8 mg, 30.3%) as a colorless oil. 1 (29) To a mixture of 1-(3-(benzyloxy)-4-methoxyphenyl)-1-(3,4,5-trimethoxyphenyl)siletane (26b) (201.9 mg, 0.45 mmol) and ethyl acetate (5 mL) was added 5% Pd/C (20 mg) at room temperature, and the whole was stirred under an H 2 atmosphere at the same temperature for 13 h. The reaction mixture was filtered through a Celite pad and the solvent was evaporated. The residue was purified by silica gel column chromatography (hexane/ethyl acetate = 9/1 to 4/1) to give 29 (48.5 mg, 30.0%) as a colorless oil.…”
Section: -((34-dimethoxyphenyl)dimethylsilyl)-2-methoxyphenol (22)mentioning
confidence: 97%
“…These resemble the interactions of the 3,4,5-trimethoxy group of colchicine in the hydrophobic cavity of tubulin. [65] The binging pose of 11 x suggested that the pyridin-2-yl group forms hydrophobic interactions with aAsn101. In addition, the model also suggests that hydrogen bonding interactions form between the carbonyl group of prop-2-ene-1-one and aAsn101, in the range of 2.6-2.8 ( Figure 11).…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…Recently, in the colchicine-binding domain, three zones of interaction were identified and specific amino acids responsible for the recognition and binding of known MIAs were determined [106]. Advanced in silico studies with the use of pharmacophore models were included in order to identify the most active cis-stilbene derivatives worthy of further synthesis.…”
Section: Molecular Modeling and Virtual Screeningmentioning
confidence: 99%
“…For the β subunit, eight isoforms exerting 90% similarity have been identified and for the α subunit, at least six different isoforms are known [106]. They are characterized by different tissue distribution in normal cells, and in cancer cells, they may interact differently with chemotherapeutics.…”
Section: Molecular Modeling and Virtual Screeningmentioning
confidence: 99%